Hubungan antara Pola Asuh Orang Tua dengan Kepercayaan Diri pada Anak Menurut Orang Tua di TK - Novita, Asih Rena; Syuraini, Syuraini (Penerbit Aksara Rentaka Siar (ARS), 2019)
This research was motivated by the low self-esteem of children in Talang Sari Nagari Kindergarten Lunang II Kecamatan Lunang Kabupaten Pesisir Selatan. This study aims to describe: (1) parenting parents, (2) children's self-confidence, (3) the relationship between parenting parents and self-confidence in children. This research includes correlational quantitative research. The population in this study was 25 parents of students at Talang Sari Kindergarten. The sample of this study was taken 80% of the population, namely 20 parents of students using the stratified random sampling technique. The technique of collecting data uses a questionnaire. Data analysis techniques use Rank Order. The results showed that: (1) poor parenting parents, (2) children's self-confidence are still low, and (3) there is a significant parent's Talang Sari Kindergarten Nagari Lunang II Kecamatan Lunang Kabupaten Pesisir Selatan. The suggestion that parents can apply proper parenting to their children so that they can increase children's self-confidence and can be used as reading material about parenting in shaping children's self-confidence.